The CCSDS 123.0-B-2 "Low-Complexity Lossless and Near-Lossless Multispectral and Hyperspectral Image Compression" Standard: A comprehensive review - Hernandez-Cabronero, Miguel; Kiely, Aaron B.; Klimesh, Matthew; Blanes, Ian; Ligo, Jonathan; Magli, Enrico; Serra-Sagrista, Joan (IEEE geoscience and remote sensing magazine, 2021)
The Consultative Committee for Space Data Systems (CCSDS) published the CCSDS 123.0-B-2, "Low-Complexity Lossless and Near-Lossless Multispectral and Hyperspectral Image Compression" standard. This standard extends the previous issue, CCSDS 123.0-B-1, which supported only lossless compression, while maintaining backward compatibility. The main novelty of the new issue is support for near-lossless compression, i.e., lossy compression with user-defined absolute and/or relative error limits in the reconstructed images. This new feature is achieved via closed-loop quantization of prediction errors. Two further additions arise from the new near-lossless support: first, the calculation of predicted sample values using sample representatives that may not be equal to the reconstructed sample values, and, second, a new hybrid entropy coder designed to provide enhanced compression performance for low-entropy data, prevalent when nonlossless compression is used. These new features enable significantly smaller compressed data volumes than those achievable with CCSDS 123.0-B-1 while controlling the quality of the decompressed images. As a result, larger amounts of valuable information can be retrieved given a set of bandwidth and energy consumption constraints.